Tyrosine-free amino acid mixtures reduce physiologically-evoked release of dopamine in a selective and activity-dependent manner. (June 2014) - Le Masurier, Marisa; Zetterström, Tyra; Cowen, Philip; Sharp, Trevor
Depletion of the catecholamine precursor tyrosine using tyrosine-free amino acid mixtures is an important tool in neuropsychological studies, and often considered dopamine selective on the basis of neuropharmacological studies. However, little is known of the effects of tyrosine depletion when catecholamine neurons are activated physiologically. Here we investigated the effect of tyrosine-free amino acid mixtures on catecholamine release evoked in vivo using a stimulation paradigm aimed to approximate the phasic firing pattern of these neurons that accompanies cognitive and behavioural change. Dopamine and noradrenaline release was monitored by microdialysis in rat medial prefrontal cortex (mPFC) and striatum (chloral hydrate anaesthesia, perfusion medium containing 1 µM cocaine). Electrical stimulation of the medial forebrain bundle (MFB) caused a short-lasting, frequency-dependent increase in dopamine and noradrenaline. A full tyrosine-free amino acid mixture reduced the release of dopamine in mPFC and striatum, across a range of stimulation frequencies, and the effect was greater as stimulation frequency increased. Similar results were obtained using a smaller tyrosine-free amino acid mixture. In the same experiments showing decreased dopamine, neither tyrosine-free mixture of amino acids significantly altered stimulation-evoked release of noradrenaline. These results show that tyrosine depletion using tyrosine-free amino acid mixtures causes a selective, activity-dependent decrease in dopamine release when dopamine neurons are driven physiologically.